A cSNP Map and Database for Human Chromosome 21 - Deutsch, Samuel; Iseli, Christian; Bucher, Philipp; Antonarakis, Stylianos E.; Scott, Hamish S. (Genome Research, 2001)
Single nucleotide polymorphisms (SNPs) are likely to contribute to the study of complex genetic diseases. The genomic sequence of human chromosome 21q was recently completed with 225 annotated genes, thus permitting efficient identification and precise mapping of potential cSNPs by bioinformatics approaches. Here we present a human chromosome 21 (HC21) cSNP database and the first chromosome-specific cSNP map. Potential cSNPs were generated using three approaches: (1) Alignment of the complete HC21 genomic sequence to cognate ESTs and mRNAs. Candidate cSNPs were automatically extracted using a novel program for context-dependent SNP identification that efficiently discriminates between true variation, poor quality sequencing, and paralogous gene alignments. (2) Multiple alignment of all known HC21 genes to all other human database entries. (3) Gene-targeted cSNP discovery. To date we have identified 377 cSNPs averaging ∼1 SNP per 1.5 kb of transcribed sequence, covering 65% of known genes in the chromosome. Validation of our bioinformatics approach was demonstrated by a confirmation rate of 78% for the predicted cSNPs, and in total 32% of the cSNPs in our database have been confirmed. The database is publicly available athttp://csnp.unige.ch or http://csnp.isb-sib.ch. These SNPs provide a tool to study the contribution of HC21 loci to complex diseases such as bipolar affective disorder and allele-specific contributions to Down syndrome phenotypes.
10.1101/gr.164901